2018
DOI: 10.4254/wjh.v10.i11.849
|View full text |Cite
|
Sign up to set email alerts
|

African Americans are less likely to receive curative treatment for hepatocellular carcinoma

Abstract: AIMTo determine if racial disparities continue to exist in the treatment of hepatocellular carcinoma (HCC).METHODSA retrospective database analysis using the Nationwide Inpatient Sample was performed including patients with a primary diagnosis of HCC. Univariate and multivariate analyses were utilized to determine racial disparities in liver decompensation, treatment, inpatient mortality, and metastatic disease.RESULTSA total of 62604 patients with HCC were included consisting of 32428 Caucasian, 9726 African-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Specifically, SATB2 was induced by pancreatic ductal epithelial cells when they were exposed to chronic ethanol, a condition generates reactive oxygen species (ROS). 19 Epidemiological data suggest that poor socio-economic conditions, inadequate access to screening and treatment opportunities may create stressful and inflammatory environment, [46][47][48][49][50][51][52] which may induce SATB2. This hypothesis needs to be tested in HCC disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, SATB2 was induced by pancreatic ductal epithelial cells when they were exposed to chronic ethanol, a condition generates reactive oxygen species (ROS). 19 Epidemiological data suggest that poor socio-economic conditions, inadequate access to screening and treatment opportunities may create stressful and inflammatory environment, [46][47][48][49][50][51][52] which may induce SATB2. This hypothesis needs to be tested in HCC disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Black patients were also the least likely to undergo curative therapy for HCC compared with white and Hispanic patients. 7 Another study found that black patients were significantly less likely to undergo an LT despite similar severity of liver disease, tumor characteristics, and insurance status. 8 Insurance type has also been shown to affect access to care for patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Black patients have incidence rates 2-fold that of white patients, and in a 2018 Surveillance, Epidemiology and End Results database study, the overall 5-year survival rate for patients with HCC was lower among black patients than any other racial group. Black patients were also the least likely to undergo curative therapy for HCC compared with white and Hispanic patients . Another study found that black patients were significantly less likely to undergo an LT despite similar severity of liver disease, tumor characteristics, and insurance status .…”
Section: Introductionmentioning
confidence: 99%
“…Patients were also excluded if they did not have at least 12 months of follow up after initiation of a CFTR modulator and/or ursodiol, periods of non-continuous drug claims enrollment, and no prescription coverage for any of the enrollment period. Diagnostic codes for each of these inclusion and exclusion criteria have been widely used in previous publications[ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%